Public Policy Law in military strategy and conflict in Hybrid warfare operations in the Digital Era - Hidayati, Hidayati; Tirtayasa, Subhan; Iskandar, Putra; Nugraha, Renaldi (Edusight International Journal of Multidisciplinary Studies, 2025)
Hybrid operations constitute a complex and multifaceted national security threat, combining conventional and modern military aspects. The aim of this research is that public policy law in addressing this threat depends on military strength and the synergistic integration of defense policy and public policy. The method used is that the legal approach to hybrid operations must be adaptive, ethical, and able to bridge various government sectors and civil society. Furthermore, international cooperation and active community involvement are key to the formulation of legitimate and sustainable policies. The result of the discussion is that public policies that are responsive to the dynamics of the hybrid operations threat must also pay attention to technological developments such as artificial intelligence, cyber attacks, and drone systems that expand the modern battlefield. Law No. 3 of 2002 on State Defense, which regulates the concept of total defense involving the military and community elements in facing threats, including hybrid warfare. Therefore, the model of integration of defense policy and public policy becomes the main strategy to strengthen the resilience and security of the country in facing the evolving threat of hybrid operations